The economic organization of agriculture - Schultz, Theodore W. (New York : McGraw-Hill, 1953)
In this study, the author has made an attempt to find ways of improving the existing economic organization by eliminating or reducing the instability, or where this does not seem to the solution, by adapting the economy to the instability.
Includes bibliographical references and index.
osa 24/01/2019
Loans
Keywords: Agriculture